Evolutionary analysis of genes associated with the sense of balance in semi-aquatic mammals - Yuehuan Dong; Qinguo Wei; Guolei Sun; Xiaodong Gao; Tianshu Lyu; Lidong Wang; Shengyang Zhou; Xibao Wang; Yongquan Shang; Lupeng Shi; Honghai Zhang (BMC Ecology and Evolution)
Abstract Background Semi-aquatic mammals represent a transitional phase in the evolutionary spectrum between terrestrial and aquatic mammals. The sense of balance is crucial for mammalian locomotion, and in semi-aquatic mammals, the structural foundation of this sense (the vestibular system) shows distinct morphological adaptations to both aquatic and terrestrial environments compared to their terrestrial counterparts. Despite this, the precise molecular mechanisms driving these adaptations remain elusive. Our study endeavors to unravel the genetic components associated with the sense of balance in semi-aquatic mammals and to examine the evolutionary trajectories of these genes, shed light on the molecular mechanisms underlying the adaptive evolution of balance perception in semi-aquatic mammals. Results We selected 42 mammal species across 20 orders, 38 families, and 42 genera for analysis. We analyzed a comprehensive set of 116 genes related to the vestibular system's development or function. Our findings indicate that 27 of these genes likely experienced adaptive evolution in semi-aquatic mammals. Particularly, genes such as SLC26A2, SOX10, MYCN, and OTX1 are implicated in collectively orchestrating morphological adaptations in the semicircular canals to suit semi-aquatic environments. Additionally, genes associated with otolith development, including SLC26A2, OC90, and OTOP1, likely regulate otolith sensitivity across various locomotor modes. Moreover, genes linked to vestibular disorders, such as GJB2, GJB6, and USH1C, may provide a molecular foundation for averting vertigo amidst intricate locomotor scenarios in semi-aquatic mammals. Conclusions Our research offers insights into the molecular mechanisms underlying the evolution of the sense of balance in semi-aquatic mammals, while also providing a new research direction for the adaptive evolution of mammals undergoing a secondary transition to an aquatic lifestyle.